1982
DOI: 10.1021/ac00239a028
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nitrated polycyclic aromatic hydrocarbons in diesel particulates

Abstract: The analysis of nitrated polycyllc aromatic hydrocarbons (nltro-PAH) In diesel particulate extracts using a combination of high-performance liquid chromatography, gas chromatography/mass spectrometry, hlgh-resolutlon mass spectrometry, and mass spectrometry/mass spectrometry (MS/MS) techniques Is described. Triple stage quadrupole (TSQ)-MSZMS operated In the constant neutral loss mode Is described for the rapid qualitative screening of nltro-PAH Isomer groups In solvent extracts of diesel particulates. Twenty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
87
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(93 citation statements)
references
References 13 publications
4
87
0
Order By: Relevance
“…Nitrated polycyclic aromatic hydrocarbons (NPAHs) are also a class of mutagens/carcinogens found in the atmosphere, and some of them exhibit stronger mutagenicity/carcinogenicity than their parent PAHs. 1) 1-Nitropyrene (1-NP) is believed to be emitted into the atmosphere from combustion processes of fossil fuel such as diesel fuel 2) and is one of the most abundant NPAHs in the atmosphere. 3) 1-NP taken up by humans and animals is metabolized to hydroxynitropyrenes (OHNPs; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrated polycyclic aromatic hydrocarbons (NPAHs) are also a class of mutagens/carcinogens found in the atmosphere, and some of them exhibit stronger mutagenicity/carcinogenicity than their parent PAHs. 1) 1-Nitropyrene (1-NP) is believed to be emitted into the atmosphere from combustion processes of fossil fuel such as diesel fuel 2) and is one of the most abundant NPAHs in the atmosphere. 3) 1-NP taken up by humans and animals is metabolized to hydroxynitropyrenes (OHNPs; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…5) Particulates in DE adsorb many chemicals, such as polycyclic aromatic hydrocarbons (PAHs). [6][7][8][9] We previously showed that several PAHs and monohydroxy PAHs (OHPAHs) have estrogenic/antiestrogenic and antiandrogenic activities in vitro. [10][11][12][13] Though the inhalation of DE during the formative period affects the differentiation process of the fetal organs, little is known about whether PAHs transfer from mother to offspring and act as endocrine disrupters in the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Nitroarenes are produced by the incomplete combustion of organic compounds such as fossil fuels, [1][2][3] and are also produced in the atmosphere from parent arenes and nitrogen oxides. [4][5][6] Nitroarenes are widespread environmental pollutants [7][8][9] and some are suspected human carcinogens.…”
Section: Introductionmentioning
confidence: 99%